Revealing the role of N heteroatoms in noncovalent aromatic interactions by ultrafast intermolecular coulombic decay - Zhou, Jiaqi; Jia, Shaokui; Xue, Xiaorui; Skitnevskaya, Anna D.; Wang, Enliang; Wang, Xing; Hao, Xintai; Zeng, Qingrui; Kuleff, Alexander I.; Dorn, Alexander; Ren, Xueguang (The journal of physical chemistry letters, 2024)
Despite the widely recognized importance of noncovalent interactions involving aromatic rings in many fields, our understanding of the underlying forces and structural patterns, especially the impact of heteroaromaticity, is still incomplete. Here, we investigate the relaxation processes that follow inner-valence ionization in a range of molecular dimers involving various combinations of benzene, pyridine, and pyrimidine, which initiate an ultrafast intermolecular Coulombic decay process. Multiparticle coincidence momentum spectroscopy, combined with ab initio calculations, enables us to explore the principal orientations of these fundamental dimers and, thus, to elucidate the influence of N heteroatoms on the relative preference of the aromatic π-stacking, H-bonding, and CH−π interactions and their dependence on the number of nitrogen atoms in the rings. Our studies reveal a sensitive tool for the structural imaging of molecular complexes and provide a more complete understanding of the effects of N heteroatoms on the noncovalent aromatic interactions at the molecular level.